EVALUATION OF CLINICAL EFFECTIVENESS OF MODIFIED FIXED TWIN BLOCK APPLIANCE IN THE TREATMENT OF SKELETAL CLASS II MALOCCLUSION WITH VERTICAL GROWTH PATTERN - Toshniwal, Dr. N. G.; Soni, Dr. Uday Nandkishorji; Gharat, Dr. Ninad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The modified fixed twin block is an efficient, uncomplicated myofunctional appliance for the correction of skeletal class II malocclusion in late pubertal growth spurt in noncompliant patients.